2016
DOI: 10.1080/09168451.2015.1083401
|View full text |Cite
|
Sign up to set email alerts
|

Vba4p, a vacuolar membrane protein, is involved in the drug resistance and vacuolar morphology of Saccharomyces cerevisiae

Abstract: In the vacuolar basic amino acid (VBA) transporter family of Saccharomyces cerevisiae, VBA4 encodes a vacuolar membrane protein with 14 putative transmembrane helices. Transport experiments with isolated vacuolar membrane vesicles and estimation of the amino acid contents in vacuoles showed that Vba4p is not likely involved in the transport of amino acids. We found that the vba4Δ cells, as well as vba1Δ and vba2Δ cells, showed increased susceptibility to several drugs, particularly to azoles. Although disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…On the one hand, the vacuole could sequester drugs, preventing them from harming the cell. In support of this possibility, there is evidence that yeast has multiple drug/H + antiporters that belong to the major facilitator superfamily (MFS), at least one of which, Vba4p, is localized to the vacuole [50]. Alterations in the pH of the vacuole is likely to affect the function of these antiporters.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the vacuole could sequester drugs, preventing them from harming the cell. In support of this possibility, there is evidence that yeast has multiple drug/H + antiporters that belong to the major facilitator superfamily (MFS), at least one of which, Vba4p, is localized to the vacuole [50]. Alterations in the pH of the vacuole is likely to affect the function of these antiporters.…”
Section: Discussionmentioning
confidence: 99%
“…Vba1, Vba2, and Vba3 are MFS proteins that catalyze the transport of basic amino acids into the vacuole (97). Subsequent studies suggested that Vba1 may transport other neutral and acidic amino acids (98). The initial study by Shimazu et al (97) identified two other potential family members based on sequence similarity.…”
Section: Specificity Of Transportersmentioning
confidence: 99%
“…The initial study by Shimazu et al (97) identified two other potential family members based on sequence similarity. One, Vba4, is a vacuolar membrane protein involved in drug resistance and vacuolar morphology rather than amino acid transport (98). The other, Vba5, is a plasma membrane transporter involved in cellular uptake of arginine and lysine (91).…”
Section: Specificity Of Transportersmentioning
confidence: 99%
“…VBA family transporters (Vba1, Vba2, and Vba3) were identified as vacuolar transporters involved in the uptake of basic amino acids, 21) but so far these transporters are suggested to have broad specificity for their substrates including basic amino acids, azoles, and quinidine. 22) Another member of vacuolar MFS, Atg22, was first identified as a factor required for the breakdown of autophagic bodies derived from the fusion of autophagosomes with vacuoles during autophagy. 23) It is believed that Atg22 exports amino acids out of the vacuole, because the neutral amino acids increased in the vacuoles of atg22Δ strain under nutrient-rich conditions.…”
Section: Major Facilitator Superfamily (Mfs)mentioning
confidence: 99%